127 Modeling Traumatic Brain Injury Using Human Cerebral Organoids. (April 2023) - Tallat, Ahmed Mohamed; Beltrán, Susana; Bobo, Justin; Kodavali, Chowdari; Edwards, Lincoln; LeDuc, Philip; Zinn, Pascal O.
Abstract : INTRODUCTION: Traumatic brain injury (TBI) is a leading cause of morbidity and mortality worldwide. The ability to model pathophysiological processes through 3D cultures systems may enable new treatments while eliminating the need for animal and human testing. Advances in 3D cell culture systems have resulted in the generation of human cerebral organoids, which to a great extent recapitulate key neural cytoarchitectural features. We currently have no in-vitro human TBI model. METHODS: We generated cerebral organoids from human embryonic stem cells. After maturation, the organoids were subjected to a custom-designed Mechanical Excitation Testbed (MET) that delivered compressed the organoid with controlled strain rates and strain for a given number of pulses. We investigated the repercussions of organoid compression by assessing the neuronal function, calcium signaling, and morphological changes, electrophysiology, real-time calcium imaging, and immunohistochemistry. Molecular and gene ontology analysis was also performed using RNA-seq and Ingenuity Pathway Analysis/Gene Set Enrichment. RESULTS: Our results demonstrated significant real-time calcium signaling upregulation and altered neuronal activity consistent with TBI severity. Moreover, RNA-seq data demonstrate unsupervised clustering of gene activity of moderate and severe TBI. Furthermore, gene enrichment analysis identified 3 key genes ENO1, CARD9, and FOXP3 which are associated with neuronal development, regulation of cellular apoptosis & IL-17 mediated inflammation pathway, and immunoregulation of T-cells respectively. Finally, TBI response pathways were identified involving stromal elasticity, and extracellular matrix, consistent with TBI. CONCLUSIONS: This in-vitro brain organoid TBI model shows strong phenotypic and genetic similarities with TBI patients. Furthermore, This novel TBI model could provide a basis for a high-throughput personalized patient-less model that could be used to study TBIs and test potential therapeutic modalities.